National Geographic atlas of beer : a globe-trotting journey through the world of beer - Hoalst-Pullen, Nancy; Patterson, Mark (Professor of geography) (National Geographic, 2017)
This illustrated beer atlas includes more beers and more countries than many books of its kind. Includes beer recommendations from Garrett Oliver, the renowned brewmaster of Brooklyn Brewery, and written by "beer geographers" Nancy Hoalst-Pullen and Mark Patterson, this guide features more than 100 maps and 200 color photos. You'll find beer history, trends, and tasting across six continents (and how to order a beer in 14 languages!). Travel tips include the best breweries, beer festivals, and pubs in each location.